Create positive habits - Bushman, Susanne M., 1994- ([Minneapolis, Minnesota] : Jump!, Inc., 2020)
"In this book, readers learn the benefits of positive habits, ways to form them, and how to use them to enhance mindfulness. Forming positive habits helps readers create constructive attitudes, build confidence, and foster positive peer networks. Social and emotional learning (SEL) concepts support growth mindset throughout, while Try This! and Grow with Goals activities at the end of the book further reinforce the content. Vibrant, full-color photos and carefully leveled text engage young readers as they learn more about creating positive habits. Includes sidebars, a table of contents, glossary, index, and tips for educators and caregivers. Create Positive Habits is part of Jump!'s The Sky's the Limit series"--
Good habits -- Forming habits -- Habits for your mind.
Includes index.
Ages 7-10
Keywords: Habit -- Juvenile literature; Self-care, Health -- Juvenile literature; Habit; Health self-care.; Literature